Risk of primary liver cancer in acute hepatic porphyria patients: A matched cohort study of 1244 individuals. (2nd March 2022) - Lissing, Mattias; Vassiliou, Daphne; Floderus, Ylva; Harper, Pauline; Bottai, Matteo; Kotopouli, Marianna; Hagström, Hannes; Sardh, Eliane; Wahlin, Staffan
Abstract: Background: The acute hepatic porphyrias (AHP) are associated with a risk of primary liver cancer (PLC), but risk estimates are unclear, and what AHP characteristics that predict PLC risk are unknown. In this register‐based, matched cohort study, we assessed the PLC risk in relation to biochemical and clinical porphyria severity, genotype, age, and sex. Methods: All patients in the Swedish porphyria register with acute intermittent porphyria (AIP), variegate porphyria (VP), or hereditary coproporphyria (HCP) during 1987‒2015 were included. This AHP cohort was compared with age‐, sex‐, and county‐matched reference individuals from the general population. National register‐based hospital admissions for AHP were used to indicate the clinical severity. For AIP, the most common AHP type, patients were stratified by genotype and urinary porphobilinogen (U‐PBG). Incident PLC data were collected from national health registers. Results: We identified 1244 individuals with AHP (1063 [85%] AIP). During a median follow‐up of 19.5 years, we identified 108 incident PLC cases, including 83 AHP patients (6.7%) and 25 of 12, 333 reference individuals (0.2%). The adjusted hazard ratio for AHP‐PLC was 38.0 (95% confidence interval: 24.3‒59.3). Previously elevated U‐PBG and hospitalizations for porphyria, but not AIP genotype or sex, were associated with increased PLC risk. Patients aged >50 years with previously elevated U‐PBG ( n = 157) had an annual PLC incidence of 1.8%. Conclusion: This study confirmed a high PLC risk and identified a strong association with clinical and biochemical AIP activity. Regular PLC surveillance is motivated in patients older than 50 years with a history of active AIP. Abstract :